A regenerable electrochemiluminescence aptasensor incorporating poly(ethylenimine) and thiosemicarbazide as dual co-reactants for signal amplification. (20th December 2015) - Hong, Lin-Ru; Wang, Ji-Peng; Zhuo, Ying; Chai, Ya-Qin; Zhao, Min; Gui, Guo-Feng; Yuan, Ruo
Graphical abstract: Abstract: A regenerable electrochemiluminescence aptasensor for thrombin (TB) has been developed using dual co-reactants of poly(ethylenimine) (PEI) and thiosemicarbazide (TSC) for signal amplification. Herein, Au nanoparticle (AuNPs) were in-situ electrodeposited on glassy carbon electrode (GCE) in advance, and then the colloidal gold nanoparticle (nano-Au) and TSC were alternately self-assembled on AuNPs/GCE to obtain nano-Au/TSC/AuNPs multi-layers for 5'-thiolated partly complementary strand (PCS) immobilization. Subsequently, the multifunctional binding aptamer (MBA), consisted of an adenosine triphosphate (ATP) binding aptamer (ABA) and a thrombin binding aptamer (TBA), was hybridized with PCS to generate double-strands DNA (PCS/MBA). Meanwhile, the signal probe was fabricated by immobilizing detection thrombin aptamer (TBA 2) on the surface of PEI enhanced Ru(bpy)3 2+ doped nanospheres. On the basis of sandwich-type tactics, TB was measured quantitatively in the range from 1 × 10 −5  nM to 0.1 nM. More importantly, the aptasensor could regenerate by treating with ATP to take off MBA based on ATP-induced conformation change, leaving only PCS onto the modified electrode to re-hybridize with MBA. The proposed aptasensor exhibited good selectivity, acceptable stability and satisfactory regenerability.